Dyspnea in Acute Myeloid Leukemia – An Uncommon Presentation of Diffuse Alveolar Hemorrhage - Maini, Ruby; Regmi, Manjari Rani; Tandan, Nitin; Parajuli, Priyanka; Garcia, Odalys Estefania Lara (Archives of Clinical and Medical Case Reports, 2020)
Diffuse alveolar hemorrhage is a life-threatening condition characterized by acute hypoxic respiratory failure, hemoptysis, and acute blood loss anemia. Most common etiologies are related to systemic vasculitis due to ongoing vessel inflammation. Diagnosis, however, can be challenging due to variety of non-specific symptoms. We present a challenging case of a 65-year-old male with newly diagnosed acute myeloid leukemia undergoing induction chemotherapy who developed diffuse alveolar hemorrhage.